The Role of Family Education in Forming Children’s Morals: A Critical Review from an Islamic Perspective - Muthi’ Nur Hanifah; Muhammad Irwan Padli Nasution (ANWARUL, 2025)
Family education plays a pivotal role in children’s moral development because the family functions as the primary and central locus of education from birth. This study aims to analyze the role of family education in shaping children’s morals from an Islamic perspective, with a specific focus on its underlying concepts, educational methods, and developmental stages. Employing a library research methodology, the study reviews and synthesizes relevant books, journal articles, and scholarly works on family education and children’s morals in Islam. The findings indicate that Islamic family education is grounded in Qur’anic and Hadith values, positioning parents as primary educators and role models in instilling faith, worship, and moral conduct. Moral formation is carried out through complementary educational approaches, including exemplification, habituation, advice, and educative rewards and punishments, which together support the internalization of moral and spiritual values. Furthermore, effective moral education in the family must be aligned with children’s developmental stages to ensure that messages and practices are appropriate and impactful. The study concludes that conscious, directed, and continuous family education makes a substantial contribution to fostering faithful, morally upright, and socially responsible children, thereby reinforcing the central role of the family in Islamic education and highlighting the need for strengthening value-based parenting practices.